2014
DOI: 10.3892/ijo.2014.2768
|View full text |Cite
|
Sign up to set email alerts
|

SPAG6 silencing inhibits the growth of the malignant myeloid cell lines SKM-1 and K562 via activating p53 and caspase activation-dependent apoptosis

Abstract: SPAG6, which is a novel cancer-testis antigen, is overexpressed in myeloid malignancies. Previously, SPAG6 was found in UPD (uniparental disomy) region of myeloid cell DNA from MDS patients and reported that SPAG6 may be a predictive marker of minimal residual disease in pediatric acute myeloid, but the biological role of SPAG6 in myeloid malignancies remains unclear. The present study was undertaken to determine the expression and functional significance of SPAG6 in malignant myeloid hematologic cell lines. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 33 publications
(29 reference statements)
7
28
0
Order By: Relevance
“…However, in this study, SKM-1 cells were subcutaneously injected and solid tumors were formed in NOD/SCID mice. The same phenomenon was observed in another study (28), in which both SKM-1 cells and K562 cells were transplanted subcutaneously and solid tumors formed in immunodeficient mice. This discrepancy may attribute to the fact that the microenvironments provided by these mice are not identical to those for humans, although they are suitable for MDS cell-derived tumor growth.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, in this study, SKM-1 cells were subcutaneously injected and solid tumors were formed in NOD/SCID mice. The same phenomenon was observed in another study (28), in which both SKM-1 cells and K562 cells were transplanted subcutaneously and solid tumors formed in immunodeficient mice. This discrepancy may attribute to the fact that the microenvironments provided by these mice are not identical to those for humans, although they are suitable for MDS cell-derived tumor growth.…”
Section: Discussionsupporting
confidence: 81%
“…Protein lysate was extracted from cells using RIPA lysis buffer supplemented with 1 µM PMSF (Beyotime), and protein concentration was measured with BCA Protein Assay kit (Beyotime). Western blotting was performed as previously described (28). The following primary antibodies were used in this study: rabbit anti-human cleaved-caspase-3, cleaved-caspase-8, cleaved-caspase-9, Bcl-w and Bax (immunoway, Newark, DE, USA); rabbit polyclonal antibody against human CDC40 (Abcam, Cambridge, UK); horseradish peroxidase-conjugated goat anti-rabbit IgG (Beyotime) was used as second antibody in this study.…”
Section: Quantitative Reverse Transcriptase-polymerase Chain Reactionmentioning
confidence: 99%
“…A preliminary study indicated that a high expression of SPAG6 is connected with apoptosis resistance in SKM-1 and K562 (13). In this study, when SKM-1 cells were treated with different concentrations of rTRAIL, the apoptosis rates showed an increased tendency.…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, SPAG6 is highly expressed at the break point of t(10;11)(p12;q14) in patients with CALM/AF10-positive leukemias (12). In our previous study, when the expression of SPAG6 was silenced by SPAG6-shRNA lentivirus, the growth of SKM-1 and K652 was markedly inhibited, and apoptosis was increased (13). The above evidence indicates that SPAG6 may promote cellular growth by preventing apoptosis.…”
Section: Introductionmentioning
confidence: 83%
“…Based on all these observations, we selected the genes SPAG6 (Sperm Associated Antigen 6) and L1TD1 (LINE-1 Type Transposase Domain Containing 1) for detailed investigation. SPAG6 is located in the chromosomal region 10p12.2 and is thought to be a cancer-testis antigen (CTA) [18]. CTAs represent a large family of cancer-associated antigens which are expressed in immunoprivileged tissues such as testis but were also detected in tumor tissues of various origins including lung cancer [19].…”
Section: Introductionmentioning
confidence: 99%